AN APPLICATION OF LOW-INVASIVE ACCESS IN ULTRASOUND-GUIDED SURGERY OF LIQUID FORMATION OF THE ABDOMINAL CAVITY AND RETROPERITONEAL SPACE - D. B. Demin; A. V. Laikov; M. S. Funygin; A. A. Chegodaeva; Yu. Yu. Solodov; K. V. Butina (Вестник хирургии имени И.И. Грекова)
The article presents a low-invasive method in the intraoperative ultrasound-guided surgery. The method had several steps: an access (2–3 cm) was made to a liquid formation with the following aspiration of contents, a necrotic detritus was removed through the wound tract using simultaneous ultrasound examination of efficacy of emptying the cavity with drainage. This means allowed the performance of single-stage sanitization and drainage of cavity formations, which contained the liquid and dense necrotic tissues in the lumen. The method was effective, technically workable in any surgical hospital. At the same time, it was economically reasonable, because there wasn’t need to buy an additional equipment. The application of the means considerably shortened a hospital stay and the lethality was reduced.